Strategi Kesantunan Permintaan Bahasa Jepang dalam Drama "Engine" - Satyanto Satyanto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This paper examines the variations of request strategies based on the theory suggested by Ide Sachiko on Japanese politeness strategies. The purpose of this study is figure out the variations of politeness strategy in Japanese request. The primary data source of this research a Japanese drama entitled "Engine". The data were analyzed based on the Wakimae (Discernment) and Ishiryoku (Volition) concept. Japanese social rules encourage people to take into account the social distance, psychological distance, and formality in every interaction. The distance affects the selection and use of diverse futsuugo and keigo in both request topic sentence and supporting reasons and yobikake usage preference. The results of the study show that the use of yobikake, requests, and reasons were adjusted based on the social distance of the people in the conversation.